Evaluation of the effects of melting phenomenon on the residual stress formation in ferritic pipeline multi pass girth-weld joints. (2016) - Darmadi, Djarot B.
Coupled thermo-metallurgy-mechanical (TMM) analysis using FEM was carried out to represent a girth welding in ferritic pipeline steel. One of the crucial points to predict residual stress especially in multi pass welding is how to model material behaviour when melting takes place. When elements melt, they lose stiffness and also remaining plastic strain. Based on literature, it is suggested that this stiffness and plastic strain mitigation occurs even below melting temperature, known as annealing temperature. In this paper three FEM models are evaluated: 1) model without omitting stiffness and plastic strain; 2) with mitigating stiffness and plastic strain at melting point (1, 400°C); 3) with mitigating stiffness and plastic strain at annealing temperature (970°C). Residual stress of two specimens was measured to validate the FEM models where model with 970°C of omitting stiffness and plastic strain showed best matching results.